2022
DOI: 10.1002/mds.29009
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, Glycated Hemoglobin (HbA1c), and Neuroaxonal Damage in Parkinson's Disease (MARK‐PD Study)

Abstract: Background Diabetes is associated with incidence and prevalence of Parkinson's disease (PD). Furthermore, glycated hemoglobin (HbA1c) levels have been linked with motor function and progression. Objectives We evaluated the relationship between prevalent diabetes and HbA1c levels with serum neurofilament light chain (NfL) levels as marker of neuroaxonal damage. Methods NfL concentrations were analyzed with Simoa in serum of 195 PD patients with available HbA1c values. Motor (MDS‐UPDRS III, Hoehn & Yahr [H&Y]) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…We read with interest Uyar and colleagues’ recent report on the association between diabetes, non-diabetic elevated glycated hemoglobin levels (HbA1c) and neuroaxonal damage in PD patients from the MARK-PD study. (1) The authors confirmed previously established findings of an inverse association between diabetes and cognitive and motor status. The authors also demonstrated higher serum neurofilament light (NfL) levels (a marker of neuroaxonal damage) (2) in PD patients with prevalent type 2 diabetes and in PD patients with non-diabetic elevated HbA1c levels.…”
Section: Main Textsupporting
confidence: 86%
“…We read with interest Uyar and colleagues’ recent report on the association between diabetes, non-diabetic elevated glycated hemoglobin levels (HbA1c) and neuroaxonal damage in PD patients from the MARK-PD study. (1) The authors confirmed previously established findings of an inverse association between diabetes and cognitive and motor status. The authors also demonstrated higher serum neurofilament light (NfL) levels (a marker of neuroaxonal damage) (2) in PD patients with prevalent type 2 diabetes and in PD patients with non-diabetic elevated HbA1c levels.…”
Section: Main Textsupporting
confidence: 86%
“…We appreciate the letter by Vijiaratnam and colleagues, which confirms the association of diabetes with increased neuronal damage in patients with Parkinson's disease (PD) independent of age, body mass index, and vascular risk factors 1 . PD patients with diabetes revealed increased serum neurofilament light (sNfL) chain levels in both the biomarkers in Parkinson's disease (MARK‐PD) and Tracking Parkinson's Disease studies 1,2 . However, disease duration was much longer (12 years vs. 1 year), Hoehn & Yahr stage was more advanced (2.5 vs. 1.8), and Movement Disorder Society–Sponsored Revision of the Unified Parkinson's Disease Rating Scale III score was slightly higher (26 vs. 23) in the MARK‐PD study, whereas age and Montreal Cognitive Assessment scores were identical (ie, 68 years and 25 points, respectively) 1,2 .…”
mentioning
confidence: 89%
“…PD patients with diabetes revealed increased serum neurofilament light (sNfL) chain levels in both the biomarkers in Parkinson's disease (MARK‐PD) and Tracking Parkinson's Disease studies 1,2 . However, disease duration was much longer (12 years vs. 1 year), Hoehn & Yahr stage was more advanced (2.5 vs. 1.8), and Movement Disorder Society–Sponsored Revision of the Unified Parkinson's Disease Rating Scale III score was slightly higher (26 vs. 23) in the MARK‐PD study, whereas age and Montreal Cognitive Assessment scores were identical (ie, 68 years and 25 points, respectively) 1,2 . Despite these differences, prevalent diabetes was associated with increased neuronal damage quantified by sNfL in early‐ and late PD underlining the robustness of this finding.…”
mentioning
confidence: 99%
“…We appreciate the letter by Vijiaratnam and colleagues, which confirms the association of diabetes with increased neuronal damage in patients with Parkinson's disease (PD) independent of age, body mass index, and vascular risk factors. 1 PD patients with diabetes revealed increased serum neurofilament light (sNfL) chain levels in both the biomarkers in Parkinson's disease (MARK-PD) and Tracking Parkinson's Disease studies. 1,2 However, disease duration was much longer (12 years vs. 1 year), Hoehn & Yahr stage was more advanced (2.5 vs. 1.8), and Movement Disorder Society-Sponsored Revision of the Unified Parkinson's Disease Rating Scale III score was slightly higher (26 vs. 23) in the MARK-PD study, whereas age and Montreal Cognitive Assessment scores were identical (ie, 68 years and 25 points, respectively).…”
Section: Reply To: "Diabetes and Neuroaxonal Damage Inmentioning
confidence: 99%
“…1 PD patients with diabetes revealed increased serum neurofilament light (sNfL) chain levels in both the biomarkers in Parkinson's disease (MARK-PD) and Tracking Parkinson's Disease studies. 1,2 However, disease duration was much longer (12 years vs. 1 year), Hoehn & Yahr stage was more advanced (2.5 vs. 1.8), and Movement Disorder Society-Sponsored Revision of the Unified Parkinson's Disease Rating Scale III score was slightly higher (26 vs. 23) in the MARK-PD study, whereas age and Montreal Cognitive Assessment scores were identical (ie, 68 years and 25 points, respectively). 1,2 Despite these differences, prevalent diabetes was associated with increased neuronal damage quantified by sNfL in early-and late PD underlining the robustness of this finding.…”
Section: Reply To: "Diabetes and Neuroaxonal Damage Inmentioning
confidence: 99%